A framework for priority effects. (15th June 2016) - Fukami, Tadashi; Mordecai, Erin A.; Ostling, Annette
Abstract: History of species arrival can influence plant community assembly. In this issue of the Journal of Vegetation Science, Sarneel et al. show that the strength of such historical contingency, or priority effects, varies with soil moisture in riparian plants. We discuss this study within a theoretical framework describing how and when priority effects occur via destabilizing and equalizing mechanisms. Abstract : History of species arrival can influence plant community assembly. In this issue of the Journal of Vegetation Science, Sarneel et al. show that the strength of such historical contingency, or priority effects, varies with soil moisture in riparian plants. We discuss this study within a theoretical framework describing how and when priority effects occur via destabilizing and equalizing mechanisms.